1987
DOI: 10.1002/ijc.2910400409
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of diet and gastric cancer in Northern Italy

Abstract: Dietary factors in the aetiology of stomach cancer were investigated using data from a case-control study conducted in Northern Italy on 206 histologically confirmed carcinomas and 474 control subjects in hospital for acute, non-digestive conditions, unrelated to any of the potential risk factors for gastric cancer. Dietary histories concerned the frequency of consumption per week of 29 selected food items (including the major sources of starches, proteins, fats, fibres, vitamins A and C, nitrates and nitrites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
110
3
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 198 publications
(128 citation statements)
references
References 15 publications
12
110
3
3
Order By: Relevance
“…Primary prevention of stomach cancer by dietary means is feasible by encouraging high-risk populations to decrease consumption of cured meats and salt preserved foods, and increase the consumption of vegetables and fruit. [42][43][44][45][46][47] Prevention may also be feasible through eradication of H. pylori infection, particularly in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Primary prevention of stomach cancer by dietary means is feasible by encouraging high-risk populations to decrease consumption of cured meats and salt preserved foods, and increase the consumption of vegetables and fruit. [42][43][44][45][46][47] Prevention may also be feasible through eradication of H. pylori infection, particularly in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, in the majority of case-control studies, positive associations were observed for (total) salt or sodium intake [2,3,33,34], consumption of salted fish, salted meat, pickles and soup [5,7,16,[34][35][36][37][38][39][40], adding salt to food at dinner [5,9,41], preference of salty foods [4,5,11,40,42]. The relative risks reported ranged from 1.5 to 6.7 for various measures of salt intake [14].…”
Section: Discussionmentioning
confidence: 99%
“…Most case-control studies have reported positive associations between meat products and stomach cancer risk [5, 7, 10, 15-17, 42, 47, 54, 55], but not all [9,13,33,56]. A cohort study among Hawaiians of Japanese descent reported a non-significant positive association between stomach cancer risk and the consumption of processed meats [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…32,33 This relation should, however, be considered with caution, because the estimates for bread, pasta and rice, and sugar were only marginally significant, and the association with soups may well constitute an unspecific indicator of a poor diet in this population. 34 This study has the strengths and some of the limitations of the hospital-based case-control studies. 26 In particular, the enrollment of cases and controls in major teaching and general hospital of the areas under study, and their almost complete participation indicate that selection bias is unlikely to be relevant.…”
Section: Discussionmentioning
confidence: 99%